A Case of Bilateral Hyperglycemic Nonketotic Chorea in an 83-year-old Woman With Normal Brain Imaging. Issue 2 (6th March 2023) - Khan, Fahad; Matta, Siddharth; Malik, Komal; Shayuk, Maryna
Abstract: Bilateral hyperglycemic nonketotic chorea is a rare complication of hyperglycemia. In most cases, the literature illustrates patients presenting with unilateral chorea with image findings significant for hyperintense lesions in the basal ganglia on magnetic resonance imaging (MRI) or hyperdensities on computerized tomography (CT). Here, we present a case of an 83-year-old patient who was admitted to the hospital due to acute onset of orofacial and bilateral upper extremity chorea. She had no previous history of infection, genetic mutation, neoplasms, neurodegeneration, stroke, metabolic disease, drug exposure, or autoimmune disease. Surprisingly, her MRI showed only chronic microvascular changes in periventricular white matter without basal ganglia abnormalities. However, she was noted to have marked worsening of her glycemic control over the preceding 12 months based on worsening glycated hemoglobin (HbA1c) levels and elevated serum glucose on presentation. A literature review indicates that chorea caused by hyperglycemia is at times reversible with glycemic control, but as demonstrated in our patient, this is not always necessarily the case. A similar course has only been elaborated in a few other cases in the literature. We will also review the pathogenesis, the usual disease clinical course and standard treatment from the literature.